Exploring High School Students' Understanding of Pancasila through a Film-Based Role Play Learning Model - Damayanti, Ayu Maya; Laili, Innayatul; Safiudin, Khamdan (CV. Rayyan Dwi Bharata, 2024)
This research investigates the effectiveness of the Role Play-Based Film (RPBF) learning model in enhancing high school students' understanding of Pancasila values. The findings suggest that RPBF significantly contributes to the exploration and understanding of Pancasila among high school students. This model provides a substantial contribution by creating space for direct experience, reflection, and deep contextual understanding of the noble values.The theoretical implications of this research lie in supporting social learning theories, constructivism, and social constructivism. RPBF offers an interactive learning experience, deepens collective understanding, and strengthens the emotional dimension in internalizing Pancasila values. The practical implications are substantial, as the research indicates that RPBF can be a foundation for developing more innovative and engaging curricula at the high school level. The application of RPBF not only enhances theoretical understanding but also stimulates emotional involvement and practical application of Pancasila values in daily life. However, the study has limitations, such as focusing on one learning method and constraints in generalization. Therefore, future research can explore variations in teaching methods or combinations of learning strategies and involve more representative samples. In summary, this research makes a significant contribution in the context of character education in Indonesia, providing a basis for the development of effective learning strategies to integrate Pancasila values at the high school level. Future research could further explore the long-term impacts of implementing this learning model and develop holistic teaching methods for Pancasila values education.